Comparative mapping of sex-linked genes in Lepidoptera - Nguyen, Petr (Jihočeská univerzita, 2013)
Sequenced genome of the silkmoth, Bombyx mori, allowed comparative genomic studies in Lepidoptera. The presented thesis is concerned with synteny of sex-linked genes in moths and butterflies. I took advantage of available BAC libraries and by means of fluorescence in situ hybridization I constructed physical maps of the Z chromosome of the peppered moth, Biston betularia, and the codling moth, Cydia pomonella. The results revealed unexpected dynamics of the lepidopteran Z chromosome, which was found to be involved in both inter- and intrachromosomal rearrangements.
Comparative mapping of sex-linked genes in Lepidoptera